1894 S.C. Rev. Stat. 431, ch. 28, § 490 (Vol. 2) - (:unkn) unknown (My University, 1890)
No person or corporation within the limits of this State shall sell or offer for sale any pistol, rifle, cartridge or pistol cartridge less than .45 caliber, or metal knuckles, without first obtaining a license from the county in which such person or corporation is doing business so to do.
Keywords: LICENSE - DEALERS